The role of bacterial translocation in the development of systemic inflammation in patients with cirrhosis of the liver. (Eurasian Research Bulletin, 2023)
The study included 52 patients with cirrhosis of the liver and 16 clinically healthy individuals of the control group. In all patients, the excess bacterial growth syndrome was determined using a hydrogen breath test with lactulose, the level of C-reactive protein in blood plasma and duplex scanning of unpaired vessels of the abdominal cavity with determination of their diameter, linear and volumetric blood flow rates, and for arteries - also the resistance index. The expansion of the arteries of the stomach and intestines and the growth of blood flow through them with cirrhosis of the liver are observed only in the presence of the syndrome of excessive bacterial growth. In patients with cirrhosis of the liver without the syndrome of excessive bacterial growth, the indicators of gastrointestinal blood flow practically do not differ from those of clinically healthy individuals. The development of bacterial overgrowth syndrome in cirrhosis of the liver is associated with more frequent development of ascites (OR=3.15) and varicose veins of the esophagus of the 3rd degree (OR=4.99). The blood flow through the splenic artery and vein, as well as the severity of splenomegaly and hypersplenism in cirrhosis of the liver, practically do not depend on the presence of excessive bacterial growth syndrom